Mathematics Curricula and their Desirable Characters: From the lack to production - Pacheco, Débora Reis; Ruidiaz, Paola Amaris [UNESP]; da Silva, Marcio Antonio (My University, 2024)
This work is an excerpt from ongoing doctoral research that brings to the curriculum discussions the concept of desire from a philosophical perspective. The path is trodden by the Platonic ideas of desire for lack and, afterward, this concept is confronted with the theorizations of Deleuze and Guattari. Thus, the idea of which students and teachers are desirable in the construction of curricular mathematics texts is questioned. Based on research results, it is considered that the desirable students and teachers form a social gear that contributes to a neoliberal functioning. Such a starting point allows us to problematize what has been desired in the curricula, tied to a capitalist fabrication, and how desire can be taken in other ways when considering collective movements and, thus, producing other curricular possibilities. The secondary movement, concerning the occupations of São Paulo schools in Brazil in 2015, is taken as an example in the production of another curriculum.
Currículos de Matemática e seus Desejáveis Personagens: da falta à produção
Keywords: Collectiveness; Philosophy of difference; Secondary movement; Wish. Mathematical Education